Sports wheelchair technologies - Burton, M.; Fuss, F. K.; Subic, A. (Sports Technology, 2010)
Wheelchair sports first began in the 1940s, when competitive wheelchair-based activities were devised to provide rehabilitation exercise for returning servicemen, who would use their regular "day chairs" to compete with each other in the field of play. Many advances have since taken place to improve both regular day chairs and the increasingly specialised sports wheelchairs and other associated equipment that have evolved to meet the needs of the people that use them. For example, substantially lighter materials and structures are now used in designs that result in reduced user fatigue and extend the period of comfortable manual propulsion that can be sustained. This improves the quality of everyday life for day chair users and increases the level of performance amongst wheelchair athletes. Specially developed electronic sensors and computer equipment is also used to monitor relevant performance parameters. This aids the assessment of the effectiveness of rehabilitation exercise and also assists performance training for competitive events. The main focus of this review paper is to present and describe the key technologies and research findings in the area of sports wheelchairs that are used in Paralympic sports and that rely upon direct biomechanical interaction between the user and the main drive wheels to achieve propulsion.